Kompetensi Jaga Mulut sebagai Peranti Komunikasi Interkultural - Yohanes Orong (LPPM STKIP PGRI Bandar Lampung, 2022)
This article aims to explain the importance of mouth guard competence as an intercultural communication tool. In conditions of high interaction between people and increasing encounters with people from various cultural and linguistic backgrounds, communicators are required to have high language competence, which pragmatically is referred to as mouth guard competence. This competence guarantees intercultural communication. By using a qualitative descriptive approach, namely research that provides an accurate description of certain individuals or groups regarding the circumstances and symptoms that occur, the article puts forward four main points related to mouth guard competence as an intercultural communication tool, namely 1) the importance of having awareness of the transcendence of the language function of simply as a means of gossip, 2) the importance of elevating politeness maxims, 3) the importance of understanding communication events or utterances, and 4) awareness of language contact as a reality that requires language users not to be pretentious either towards their own language or toward other people's language. .